ELECTRONIC WORD OF MOUTH, HARGA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN - Mayor, Keren Hapok; Bopeng, Louis Soemadi; Bajari, Makarius (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2025)
This study aims to test and analyze the influence of Electonic Word of Mouth, Price and Brand Image on the Purchase Decision of Brasov Cosmetic Products in Manokwari Regency. The type of research used is a quantitative approach with associative problems. The population of this study is people in Manokwari Regency who use brasov cosmetic products. The sample collection technique was non-probability sampling with a sample of 160 respondents. The primary data used is by conducting interviews and distributing questionnaires. Secondary data was obtained from journals, books, and websites related to research variables. The results of the study showed that the electronic Word of mouth variable partially affected the purchase decision of Brasov cosmetic products, the price variable partially affected the purchase decision of Brasov cosmetic products and the brand image variable partially influenced the purchase decision of Brasov cosmetic products, and the electronic word of mouth, price and brand image variables simultaneously affected the purchase decision of Brasov cosmetic products.